PHP-Based SIMPORA Application Testing Using the Blackbox Method - Mohamad Firdaus (Journal of Innovation and Computer Science, 2025)
This study aims to test the reliability and functionality of the PHP-based SIMPORA (Project and Budget Monitoring Information System) application using the blackbox testing method. This method was chosen because it focuses on validating the application's functions without directly examining the source code, allowing for performance evaluation from the end-user's perspective. The testing process involved a series of test scenarios designed to assess various key features, including project data input, budget monitoring, and result reporting. The testing results indicate that the SIMPORA application successfully meets most of the specified functional requirements, although some anomalies were identified and need to be addressed. This study provides significant contributions to ensuring the quality of the SIMPORA application and offers insights for further development. Therefore, the results of this research are expected to help improve the efficiency and effectiveness of project and budget management through the application of information technology-based solutions.